(untitled) (Revista Contexto & Educação, 2026)
Becoming a teacher is a process of difficult delimitation of a point of departure and arrival, on the contrary, it involves an experience of incompleteness. This text seeks to tell about a formative trajectory developed during a master’s research in a public school in Porto Alegre, specifically in the performance in Physical Education with middle school students. The objective is to reflect and analyze the processes of constitution of a teaching identity of a novice teacher working in school Physical Education during an ethnographic incursion. The text was structured in the following sections: beginning to teach; constructing my place as a teacher-researcher; the incoherencies of teaching; bonds of trust between teacher and students; and becoming a teacher. The notions of ethnographic practice, being affected, formative experience, and reflexivity offer important lenses to understand the ongoing processes of becoming a teacher.